Caracterización del capital social de los egresados del programa de Contaduría Pública de la Universidad del Quindío en los últimos cinco años (2013)
The following research is about characterizing the social capital of graduates of Accounting Program at the University of Quindio over the past five years. Social Capital is a very important tool in the social environment and relationships between public accountants in the society, through this work are detected elements that hinder the social development of the accounting profession by college graduates Quindío and those in the wider environment. This research evaluates the efficiency and effectiveness with which they develop social work as professional accountants and the degree of social cohesion when public accountants to complete their academic preparation and start their working lives, also assesses the ability to interact with colleagues either individually or collectively, the proper use of human resources , and the use of social networks, etc. .